Influence of Communication Skills and Organizational Culture on the Performance of Employees in Salek Water Safety Office, Banyuasin District, South Sumatera - Meira Rahmawati (International Journal of Marketing & Human Resource Research, 2021)
This study aims to investigate the influence of communication skills and organizational culture on the performance of the employees of Air Salek District Office, Banyuasin Regency, South Sumatra. Samples were selected using the saturated sample technique. Data of 45 respondents were collected through observation and questionnaires. This study implemented the multiple linear regression method to analyze data. The results evidence that partially each communication skill and organizational culture has a significant effect on employees' performance. Likewise, simultaneously communication skills and organizational culture have a significant effect on employees' performance. This insight can provide benefits for Air Salek District Office, Banyuasin Regency, South Sumatra. To improve employees' performance, the leader of this government institution should optimize the communication skills and organizational culture factors.